Cold water swimming reshapes gut microbiome to improve high-fat diet-induced obesity - Men, Jie; Cui, Chenglong; Li, Hao; Li, Zhaowei; Zhang, Yu; Liu, Zhiyu; Wang, Qi; Liu, Penghong; Zou, Shuangling; Yu, Zhengyang; Zhang, Yuxi; Wu, Simin; et al. (Frontiers in Microbiology, 2025)
Hypothermia and swimming have been shown to alleviate high-fat diet (HFD)-induced obesity, with effects linked to the gut microbiota (GM). However, whether the effects of cold water swimming (CWS) on GM can be effectively transferred through fecal microbiota transplantation (FMT) has not been investigated. This study established mice models of obesity, CWS and FMT to investigate the mechanism by which CWS reshapes GM to improve HFD-induced obesity. Additionally, we analyzed the relationship between obesity phenotypes, GM composition, gene expression and CWS. The study found that HFD induced obesity phenotypes and GM dysbiosis in mice, while CWS produced opposite effects. The FMT results confirmed that CWS effectively alleviated HFD-induced lipid accumulation, metabolic disorders, and chronic inflammatory responses, which are associated with increased GM diversity, enrichment of beneficial bacteria, and the repair of intestinal barrier damage. Furthermore, these beneficial effects can be effectively transferred via FMT. The evidence from this study suggests that GM plays a critical role in the anti-obesity effects of CWS, with intestinal barrier repair emerging as a potential therapeutic target. This also provides scientific evidence for the feasibility of FMT as a strategy to combat obesity.